Students' educational choices and future orientations in Slovenia - Živoder, Andreja (Annales. Series historia et sociologia, 2013)
The article examines the link between students' educational choices and future orientations within the framework of contemporary societal conditions. It draws on quantitative and qualitative data obtained in a survey, essays and interviews with 9th grade students in Slovenia in 2010-2011. The research results show that in the context of the increasing individualisation of societal risks, growing unpredictability and decreasing standardisation of life courses, the students consider education to be highly relevant for their future lives, and their anticipation of the future has a significant effect on their present (educational) choices. The article attempts to highlight the vital links between educational choices and expectations concerning the future, identify the key individual and structural factors of students' educational choices and future orientations and recognise the main difficulties and paradoxes of Slovenian students' planning for the future in contemporary circumstances.
Keywords: Education; Future; Izobraževanje; Occupational choice; Poklicna izbira; Prihodnost; School children; Slovenia; Slovenija; Učenci